Dental workforce shortage in Florida and access to oral health care for Military Veterans: a narrative review and strategic health management model - Paulo Vinicius de Oliveira Bastos; Larissa Carvalho Cardoso Gomes; Pedro Augusto Dias Lima; Adriano Bonguardo; Larissa Caroline Cayres Pereira; Pablo Mendonça de Souza; Suzana Carolina Ramos; Marcos Villa-Nova (South Florida Journal of Environmental and Animal Science, 2026)
Dental workforce shortages are formally documented across the United States through federal and state shortage-area designations, yet the way this shortage intersects with the unmet oral health needs of specific vulnerable populations remains underexplored in the dental management literature. This narrative review examines the intersection between the documented dental workforce shortage in the State of Florida and the oral health access gap experienced by military veterans, drawing on official data from the Health Resources and Services Administration (HRSA), the Florida Department of Health, the Florida Department of Veterans' Affairs, and the U.S. Department of Veterans Affairs, together with peer-reviewed literature on veteran oral health, post-traumatic dental-care anxiety, and the cost-effectiveness of preventive dentistry. As of January 2026, Florida required 1,271 additional dentists to eliminate its dental Health Professional Shortage Area (HPSA) designations, while only about one-quarter of the nearly nine million veterans enrolled in Veterans Health Administration (VHA) care are eligible for comprehensive dental benefits. Combat-related post-traumatic stress disorder (PTSD) is independently associated with worse periodontal indices and higher decayed-missing-filled-teeth (DMFT) scores, and trauma-informed dental protocols have been shown to reduce dental anxiety without exacerbating comorbid psychiatric symptoms. These findings are synthesized into a concrete strategic model for a veteran-focused dental clinic, addressing credentialing, trauma-informed protocols, sliding-fee access, and preventive-care cost avoidance. The study's limitations and directions for future empirical research are discussed.